Pembinaan Pembelajaran Fiqih di MI Baital Mukaddas - Sariana; Muhammad Ikbal; Irwin Hidayat; Sardiyanah (PENDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Coaching is defined as a search for educational solutions, both formal and non-formal, which is carried out consciously, planned, directed, and responsible in order to advance, guide, and develop a balanced, intact, and harmonious introduction to personality, knowledge, and skills in accordance with talents. and its ability as a provision for later on its own initiative to add, improve and grow oneself, fellow humans and their environment towards the realization of a balanced human dignity, worth, and abilities as well as an independent personality. ' understand and develop knowledge in learning fiqh.